Environmentalism and NGO accountability - Yekini, Kemi C.; Yekini, Liafisu Sina; Ohalehi, Paschal (Advances in environmental accounting & management ;, 2020)
It is increasingly being recognised across society that the preservation of our natural environment should shape political, economic and social policies. This book delves into the partnership of non-governmental organisations (NGOs), Environmental NGOs (ENGOs), their communities, and their governmental counterparts in responding to this need. Providing extended research on environmentalism and the NGOs' roles in promoting environmental accountability, the chapters present a comprehensive overview of the interaction between the two themes both regionally and internationally. Topics include the accountability of Environmental NGOs (ENGOs), impact of NGOs on environmental sustainability, NGOs and sustainable development goals, NGOs and social reporting quality, and the role of NGOs in urban and rural environmental governance. The authors present these insights within the context of developing economies, continental and global perspectives, as well as the transformational angle. This book provides readers with a truly comprehensive snapshot of the environmental accountability of NGOs.